Biology and Management of the Asian Citrus Psyllid, Diaphorina citri Kuwayama, in Florida Citrus - Michael E. Rogers; Philip A. Stansly (EDIS, 2007)
ENY-739, a 7-page illustrated fact sheet by Michael E. Rogers and Philip A. Stansly, provides information about the biology of this vector of citrus greening disease to aid growers in implementing integrated pest management (IPM) practices for suppressing the population in citrus-growing areas of Florida. It includes sections on identification and biology, psyllid feeding damage, pathogen transmission, management, and selected references. Published by the UF Department of Entomology and Nematology, June 2006.